Marginal adaptation of class V restorations with current-generation dentin-bonding agents: effect of different dentin surface treatments - Cavalheiro, Jessica P.atrícia; Tonetto, Mateus R.odrigues; Borges, Álvaro Henrique; Bandéca, Matheus C.oelho; dos Santos, Reidson S.tanley Soares; de Campos, Edson A.lves; Saad, José Roberto C.ury; Dantas, Andréa Abi R.ached; de Andrade, Marcelo F.errarezi (My University, 2014)
This study sought to assess the use of chlorhexidine with several excipients as a dentin surface treatment and its effect on marginal adaptation of class V restorations with current-generation dentin bonding agents. A total of 120 human third molars were selected and allocated into 12 groups, with standardized buccal class V restorations randomly divided into preconditioned dentin rinsed with: water; water + chlorhexidine; ethanol; or ethanol + chlorhexidine. After rinsing of dentin (previously conditioned with 35% phosphoric acid) with the test solutions, the Adper single bond 2, prime and bond 2.1, and Excite bonding systems were applied randomly. Restorations were performed with Filtek™ Z350 XT composite resin. The resulting specimens were subjected to thermal and mechanical load cycling. Quantitative analysis of marginal adaptation was performed on epoxy replicas by means of scanning electron microscopy. Results were assessed by means of the Kruskal-Wallis test (percentages of continuous margins) and Wilcoxon test (differences between percentages of continuous margins before and after thermal cycling and mechanical loading), at a significance level of p < 0.05. Outcomes in the chlorhexidine-treated groups were not superior to those obtained with other treatments.